2019
DOI: 10.3390/rs11192239
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Forest Canopy Height Using MODIS BRDF Data Emphasizing Typical-Angle Reflectances

Abstract: Forest-canopy height is an important parameter for the estimation of forest biomass and terrestrial carbon flux and climate-change research at regional and global scales. Currently, various methods combining Light Detection and Ranging (LiDAR) data with various auxiliary data, particularly satellite remotely sensed reflectances, have been widely used to produce spatially continuous canopy-height products. However, current methods in use for remote sensing reflectances mainly focus on the nadir view direction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 84 publications
1
9
0
Order By: Relevance
“…Thus, the BRDF was not investigated or assessed in this study and the impacts from BRDF can be ignored. We have focused on the assessments and evaluations of scale impacts of different resolutions ascribed from different flight altitudes [ 87 , 88 ]. Without considering the BRDF, the RGB images from flight altitude of 50 m will better fit the ground samplings.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the BRDF was not investigated or assessed in this study and the impacts from BRDF can be ignored. We have focused on the assessments and evaluations of scale impacts of different resolutions ascribed from different flight altitudes [ 87 , 88 ]. Without considering the BRDF, the RGB images from flight altitude of 50 m will better fit the ground samplings.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [ 53 ] tested angular and band effects on forest biomass retrieval and found that off-nadir vegetation indices could predict the forest biomass more accurately than the nadir. Cui et al [ 54 ] also emphasized typical angle reflectances for estimating canopy heights. In line with these studies, the proposal of VSI for the sole purpose of deriving volumetric structure of the canopy (above-ground biomass) is a timely and significant contribution.…”
Section: Discussionmentioning
confidence: 99%
“…In this work It is observed that the specular peak of BRDF is higher at 1550 nm as compared to other wavelengths and augments with the increase of the incident angle. This shows the suitability of 1550 nm to be used in the FMCW-PHRAD system to measure the reflection characteristics to offer an improved LiDAR cloud-point sensor data (Li and Liang 2015;Cui et al 2019) for different target classifications. Moreover, the BRDFs often contain specular peaks that are several orders of magnitude higher than the nearby areas.…”
Section: Target-characterizationmentioning
confidence: 93%